Intercomponent interactions in hybrid polymer composites based on chemically modified silica and silver nanoparticles - Tolstov, A. L.; Sorochynska, L.A.; Lebedev, E.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Hybrid polymer nanocomposites have been obtained via a chemical modification of fine silica by either poly(N-vinylpyrrolidone) or poly(acrylic acid) with the sequential immobilization of in situ synthesized silver nanoparticles. An influence of silver nanoparticles on the thermal properties and the thermooxidative behavior of the obtained polymer composites has been investigated. It is found that the nanofiller has a strong effect on the relaxation behavior of the polymer shell of a hybrid matrix due to its physical interaction with macromolecule chains, as well as due to the rearrangement of the intermolecular/intercomponent hydrogen bonding network. Silver-containing hybrid nanocomposites demonstrate the enhanced thermal stability.